UI/UX Design Aplikasi Belajar Online (Ayo Belajar) Menggunakan Metode Design Thinkingg - Joko Bintarto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The online learning media that has been designed and developed is called Ayo Belajar. Online learning media is a platform used to deliver learning materials to students via the internet. This learning media aims to help students learn more easily, anytime and anywhere, by accessing content in the form of text and videos.The research aims to design engaging and user-friendly learning media for students. Therefore, the UI/UX design is developed using the Design Thinking method. The process consists of five stages: initial product requirement, empathize, define, ideate, and prototype.Based on the System Usability Scale (SUS) testing results, Ayo Belajar received a